A randomised controlled trial comparing needle movements during combined spinal‐epidural anaesthesia with and without ultrasound assistance. (10th January 2018) - Chin, A.; Crooke, B.; Heywood, L.; Brijball, R.; Pelecanos, A. M.; Abeypala, W.
Summary: Ultrasound assistance for neuraxial techniques may improve technical performance; however, it is unclear which populations benefit most. Our study aimed to investigate the efficacy of neuraxial ultrasound in women having caesarean section with combined spinal‐epidural anaesthesia, and to identify factors associated with improved technical performance. Two‐hundred and eighteen women were randomly allocated to ultrasound‐assisted or control groups. All the women had a pre‐procedure ultrasound, but only women in the ultrasound group had this information conveyed to the anaesthetist. Primary outcomes were first‐pass success (a single needle insertion with no redirections) and procedure difficulty. Secondary outcomes were block quality, patient experience and complications. Exploratory sub‐group analysis and regression analysis were used to identify factors associated with success. Data from 215 women were analysed. First‐pass success was achieved in 67 (63.8%) and 42 (38.2%) women in the ultrasound and control groups, respectively (adjusted p = 0.001). Combined spinal‐epidural anaesthesia was 'difficult' in 19 (18.1%) and 33 (30.0%) women in the ultrasound and control groups, respectively (adjusted p = 0.09). Secondary outcomes did not differ significantly. Anaesthetists misidentified the intervertebral level by two or more spaces in 23 (10.7%) women. Sub‐group analysis demonstrated a benefit for ultrasound in women with easily palpable spinous processes (adjusted p = 0.027). Regression analysis identified use of ultrasound and easily palpable spinous processes to be associated with first‐pass success.